2019
DOI: 10.1158/1055-9965.epi-18-1259
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acrylamide Intake and Risk of Esophageal, Gastric, and Colorectal Cancer: The Japan Public Health Center–Based Prospective Study

Abstract: Background: Acrylamide has been classified as a probable human carcinogen based chiefly on laboratory evidence. However, the influence of dietary acrylamide intake on risk of esophageal, gastric, and colorectal cancer has not been extensively studied. We aimed to evaluate the association between dietary acrylamide intake and esophageal, gastric, and colorectal cancer using data from the Japan Public Health Center-based Prospective Study. Methods: Our study included 87,628 participants who completed a food-freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Participants were asked to report the general average consumption frequency of 138 food and beverage items, of standard portion size, in the last year [14]. The details of response choices for frequency, standard portion size, and relative portion sizes have been described elsewhere [15][16][17]. The validity and reproducibility study of the FFQ has been conducted by taking the dietary intakes from 28-day weighed dietary records (DRs) as a reference in a subcohort of the JPHC Study [18][19][20].…”
Section: Acrylamide Intake Assessmentmentioning
confidence: 99%
“…Participants were asked to report the general average consumption frequency of 138 food and beverage items, of standard portion size, in the last year [14]. The details of response choices for frequency, standard portion size, and relative portion sizes have been described elsewhere [15][16][17]. The validity and reproducibility study of the FFQ has been conducted by taking the dietary intakes from 28-day weighed dietary records (DRs) as a reference in a subcohort of the JPHC Study [18][19][20].…”
Section: Acrylamide Intake Assessmentmentioning
confidence: 99%
“…Gastric cancer is one of the most common cancers worldwide, especially in Asia, with only a 5 year survival rate of diagnosis (Liu et al, 2019;Rugge et al, 2019). Despite developments in the treatment of GC, the prognosis remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…According to laboratory evidence, ACR has been classified as a possible human carcinogen. It has also been proved that dietary acrylamide intake causes esophageal, gastric, and colorectal cancer ( Liu R. et al, 2019 ). Besides, lots of studies have proved that neurotoxicity of acrylamide in tissues and organs has been confirmed at the animal levels ( Song et al, 2008 ; Tomaszewska et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%